Kualitas Fisik, Kimia dan Mikrobiologi Susu Kambing pada Waktu Pemerahan yang Berbeda di Peternakan Cangkurawok, Balumbang Jaya, Bogor - Arifin, M.; Oktaviana, A. Y.; Wihansah, R. R. S.; Yusuf, M.; Rifkhan, Rifkhan; Negara, J. K.; Sio, A. K. (Department of Animal Production and Technology, Faculty of Animal Science, IPB University in associated with Animal Scientist's Society of Indonesia (HILPI), 2016)
The aim of this study was to determine the physical, chemistry, and microbiological quality of goat’s milk collected from morning and afternoon milking. A total of 3 of crossbred goat (PE) milk were used in this study. These samples were analyzed for total plate count (TPC), Staphylococcus sp, Escherichia coli, and Salmonella sp. Test anova shown any significant differences ( p<0,05) in Escherichia coli while another microorganisms not significant. For quality physical and chemical anova results showed no difference between morning and afternoon milking. Based on Indonesian National Standard (SNI) for fresh milk No 3141.1-2011, the level of TPC, and Salmonella sp.were still in standard range, while Staphylococcus sp.and Escherichia coli was exceed the standard value. In conclusion, raw milk of goat collected directly from the udder is safe to consume.